1988
DOI: 10.1192/bjp.153.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Neuropsychology of Schizophrenia

Abstract: A viable neuropsychology of schizophrenia requires, first, that signs and symptoms be understood in terms of underlying psychological processes and, second, that these underlying processes be related to brain systems. We propose that the negative signs of schizophrenia reflect a defect in the initiation of spontaneous action, while the positive symptoms reflect a defect in the internal monitoring of action. The spontaneous initiation of action depends upon brain systems linking the prefrontal cortex and the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
242
4
4

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(265 citation statements)
references
References 36 publications
15
242
4
4
Order By: Relevance
“…In particular, a recent study using a new conflict procedure with rhesus monkeys showed a high correlation between therapeutic potencies and the ability of benzodiazepines to increase suppressed responding. The cingulate cortex has been hypothesized to contribute to the internal monitoring of planning and controlling functions of the prefrontal cortex as well as the regulation of affective signals coming from limbic areas (Frith and Done, 1988). Others have attributed a conflict-monitoring function to this structure (Botvinick, Nystrom et al, 1999) due to its role implementing strategic processes to reduce cognitive conflicts (Carter, Macdonald et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a recent study using a new conflict procedure with rhesus monkeys showed a high correlation between therapeutic potencies and the ability of benzodiazepines to increase suppressed responding. The cingulate cortex has been hypothesized to contribute to the internal monitoring of planning and controlling functions of the prefrontal cortex as well as the regulation of affective signals coming from limbic areas (Frith and Done, 1988). Others have attributed a conflict-monitoring function to this structure (Botvinick, Nystrom et al, 1999) due to its role implementing strategic processes to reduce cognitive conflicts (Carter, Macdonald et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Broadly speaking, they consist of: 1. source monitoring deficits and 2. aberrant salience (memory-attention disturbances). Recent work on these approaches harks back to the neurocognitive work of the psychologists Frith [52,53], Gray [54][55][56] and Hemsley [57][58][59][60], experimentalists whose views were considered in a phenomenological perspective, and in relationship to self-disturbance in particular, by Sass [9]. These two streams of research will be reviewed in turn before considering ways forward in integrative models, particularly regarding the role of early neurodevelopmental disturbances, primary versus secondary disturbances, and the state versus trait nature of such pathology.…”
Section: The Phenomenological Domain: Basic Self-disturbance In Schizmentioning
confidence: 99%
“…Several authors have explained such delusions as a breakdown of the sense of agency (Frith, 1988, Frith and Done, 1989, Frith, 1992, Blakemore, et al, 2002. However, schizophrenia patients without first-rank symptoms also show sense of agency impairments, albeit to a lesser degree (Daprati et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with schizophrenia may exhibit a specific group of symptoms, so-called first-rank symptoms, which include passivity symptoms such as thought insertion or delusions of control (Blakemore et al, 2002). Patients with these symptoms experience others'actions as a consequence of their own intentions or attribute their own actions to external sources.Several authors have explained such delusions as a breakdown of the sense of agency (Frith, 1988, Frith and Done, 1989, Frith, 1992, Blakemore, et al, 2002. However, schizophrenia patients without first-rank symptoms also show sense of agency impairments, albeit to a lesser degree (Daprati et al, 1997).…”
mentioning
confidence: 99%